KAJIAN YURIDIS TERHADAP PENERAPAN PASAL 21 AYAT 1 KITAB UNDANG UNDANG HUKUM ACARA PIDANA (KUHAP) TENTANG PENAHANAN ATAU PENAHANAN LANJUTAN - Karyoto Karyoto; Oktabilla Ayu Lestari (MIZAN, Jurnal Ilmu Hukum, 2019)
because suspects or defendants are particularly vulnerable to violations of their human rights, especially in the context of law enforcement. The suspect or defendant is in the position of the examination object in the process. All series of processes, whether in the examination phase of witnesses, expert examinations, evidence collection, and other evidence collection, are directed to a suspect or defendant, either to convict or not to be guilty The aims of this study are: (1) To know the meaning of the obscurity of the norm in the sentence "in the case of a concerning circumstance" contained in Article 21 paragraph (1) of the Criminal Procedure Code on detention or continued detention. (2). To know and to learn the racial / basic establishment in the provisions of Article 21 paragraph (1) of the Criminal Procedure Code which contains "anxiety condition" in the case of further detention or detention. This research method uses conceptual approach, statute approach and historical approach. The results of the study are: Arrangement of continued detention and detention in the Criminal Procedure Code is highly subjective and tends to have a very wide and unlimited interpretation. This is a blatant disregard for the legal norms governing the detention and continued detention. Detention refers to the provisions of Article 21 of the Criminal Procedure Code requiring a further detention or detention order be made against a suspect or defendant allegedly committing a crime on the basis of sufficient evidence and escape concerns, removing evidence or reprising his crime. In the provisions of that article is contained subjective opportunities for resistance to a person. Worry obviously depends on the subjective feeling of the investigator, prosecutor or judge. The absence of the parameters in the phrase "circumstances of concern" that are not explicitly regulated, both within the Criminal Procedure Code itself and in its implementing rules, are particularly vulnerable to human rights violations, especially to suspects or defendants held without filled first in circumstances that cause concern in advance.